Pelatihan Pembuatan Kemoceng di SD Negeri Klasuat untuk Meningkatkan Kreativitas Masyarakat Papua Usia Dini - Mohammad Arief Nur Nur; Siti Nur Kayatun; Asih Ahistasari; Evi Murfrihah Zain; Mirga Maulana Rachmadhani (Abdimas: Papua Journal of Community Service, 2023)
Since the COVID-19 pandemic entered Indonesia in mid-March 2020, almost all educational activities have been suspended, and almost all schools have been closed. and universities are not running as they should. As a result, students are required to develop their thinking by making creative handicrafts, not only in education but also in themselves. A duster is a cleaning tool that can remove dust at home, school, the office, and other places. To increase the students' interest and enthusiasm for learning at SD Negeri Klasuat, Sorong City, we made an activity to make a feather duster from raffia rope. This activity taught SD Negeri Klasuat students in Sorong City how to make a duster as a dust cleaner using simple materials and tools. This activity also instills awareness of the importance of education in students.